Characterization of Escherichia coli Isolated from Day-old Chicken Fluff in Taiwanese Hatcheries - Zhao, Shengnan; Wang, Chia-Lan; Chang, Shao-Kuang; Tsai, Yi-Lun; Chou, Chung-Hsi (Avian diseases, 2019)
Avian colibacillosis resulting from avian pathogenic (APEC) seriously disrupts poultry production. Hatcheries are the main source of chickens for commercial farms. To characterize the potential pathogenicity of strains isolated from hatcheries, 2344 fluff samples from 1-day-old chickens were collected from hatching incubators between October 2016 and November 2017. Among the hatcheries, the incidence of varied from 0% to 16.9%, with an overall incidence of 2.0%. High incidences reflected inadequate sanitation in some hatcheries. We also compared 20 clinically isolated APEC strains with fluff-originated in terms of existence of 10 virulence-associated genes (VAGs) and antimicrobial-resistance genes, and antimicrobial resistance using minimum inhibitory concentration (MIC) values. Our results showed that APEC more-frequently possessed most of the assessed VAGs ( , , , , , , , , and ), suggesting that fluff-originated is less likely to cause avian colibacillosis. However, fluff-originated more-frequently expressed the adhesion gene , which could confer higher upper respiratory tract adhesion. Both APEC and fluff-originated demonstrated multidrug resistance including 100% resistance to ampicillin, amoxicillin, cephalexin, florfenicol, and trimethoprim-sulfamethoxazole. Based on median MIC values, fluff-originated was more susceptible to antibiotics. However, resistance-gene existence did not significantly differ between groups, suggesting that fluff-originated should still be a public health concern. Molecular subtyping with I-digested pulsed-field gel electrophoresis revealed that only a few strains showed identical patterns, indicating that a variety of contamination sources were present within individual hatcheries. Identical strains within the same hatchery may indicate vertical transmission from parent flocks. Overall, this is the first study to characterize fluff-originated . Our results suggest that it has lower pathogenicity than APEC and that thorough sanitation should be performed to reduce the occurrence of fluff-originated in hatcheries.